Digital Audio Visual Pop Up Book Media in the Civics Subject for Grade IV Elementary School Students Muhammadiyah 11 Medan - Darnia Darnia (Journal of Elementary School Education, 2025)
This research is motivated by the limited availability of digital media for elementary school students. In the ever-evolving digital era, the use of technology-based learning media is very important as a solution to increase learning effectiveness. This research is a development research that produces a product media in the form of a digital audio-visual pop-up book. This study aims to determine the steps for developing a digital audio-visual pop-up book media in the Civics Phase B subject at Muhammadiyah 11 Elementary School, Medan, East Medan. The type of research used is development research (Research and Development ) using the ADDIE model, namely analyze, design, development, implementation, and evaluation. The subjects of this study were fourth-grade students of Muhammadiyah 11 Elementary School, Medan. The object of this research is a digital audio-visual Pop-Up Book media with power point and capcut applications to facilitate and motivate learning abilities in Civics subjects. Data collection techniques are observation, expert validation, and questionnaires. Expert validation is media, language and material validation. The trial design is given to validators and users. The results of the development of Audio Visual Pop Up Book Media by expert validators are material experts 82% in the "very feasible" category, media experts 90% with the "feasible category", and language experts 97% with the "feasible category". The practicality test is carried out by teacher responses and student responses by giving questionnaires. The results of the development of Audio Visual Pop Up Book Media by teacher responses are 100% in the "very practical" category, and student responses are 96% in the "very practical" category, the trial was conducted on 30 fourth grade students of Muhammadiyah 11 Elementary School Medan. The results of the development of digital audio-visual pop-up book media with the material of Norms in society can arouse students' enthusiasm in learning.